2019
DOI: 10.1002/jmr.2782
|View full text |Cite
|
Sign up to set email alerts
|

The multiple flavors of GoU pairs in RNA

Abstract: Wobble GU pairs (or GoU) occur frequently within double‐stranded RNA helices interspersed within the standard G═C and A─U Watson‐Crick pairs. However, other types of GoU pairs interacting on their Watson‐Crick edges have been observed. The structural and functional roles of such alternative GoU pairs are surprisingly diverse and reflect the various pairings G and U can form by exploiting all the subtleties of their electronic configurations. Here, the structural characteristics of the GoU pairs are updated fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 77 publications
(163 reference statements)
5
33
0
Order By: Relevance
“…2a, Supplementary Figure S1). While it is often assumed that the T (or U) base primarily moves to form a wobble (Westhof et al 2019;Westhof 2014), the structures show both bases move to form the wobble pair as noted previously for G•T mismatches in A-DNA (Rabinovich et al 1988) (Fig. 2b).…”
Section: Wobble G•t Mismatches Have a Distinct Sugar-backbone Conformsupporting
confidence: 67%
“…2a, Supplementary Figure S1). While it is often assumed that the T (or U) base primarily moves to form a wobble (Westhof et al 2019;Westhof 2014), the structures show both bases move to form the wobble pair as noted previously for G•T mismatches in A-DNA (Rabinovich et al 1988) (Fig. 2b).…”
Section: Wobble G•t Mismatches Have a Distinct Sugar-backbone Conformsupporting
confidence: 67%
“…The combination of a sulfur atom in position 2 and an electron-withdrawing or electron-donating side chain in position 5 promotes various tautomeric forms of uracil, i.e., a 2,4-diketo form (K in Figure 7A,B), an E4 tautomer ( Figure 7C), or a zwitterionic ZI form ( Figure 7D). This "chameleon" ability explains how R5S2U hybridizes with an A complement (the K form) and a G complement (K, E4, or ZI forms) [44]. The latter modes (E4 and ZI) were previously demonstrated in the crystal structures of mcm5S2U 34 -tRNA (U E4 -G) and mnm5S2U-tRNA (U ZI -G) bound to mRNA models accommodated at the ribosome [41,43], and were confirmed by physicochemical and theoretical studies [45].…”
Section: Discussionsupporting
confidence: 52%
“…In contrast to the above results of thermodynamic measurements, biological experiments demonstrated that synonymous mRNA codons with 3 -A-and 3 -G-ending units are equally well recognized by tRNAs with anticodons containing wobble modified uridines, especially those containing sulfur at position 2 and bearing specific substituents at position 5 [20,38,39]. Recent data suggested that in a biological context (e.g., tRNA bound to mRNA at the ribosome), modified uridine 34 units (U* 34 ) can recognize guanosine units by at least two different hydrogen bonding patterns, depending on the substituents at positions 2 and 5 of the uracil ring [40][41][42][43][44][45]. While U* 34 -G base-pairing data are available for 5-substituted uridines and 2-thiouridines, data for corresponding 5-substituted 2-selenouridines identified in tRNAs are limited [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Modification of U34 is necessary for decoding G3 ending codons. The modification in U34 (U34*) changes the chemical structure of the U34 so that a pair U34*-G3, with the U displaced into the minor groove, and not into the major groove, can be stabilized (Rozov et al 2016;Westhof et al 2019). Several U34containing tRNAs were observed modified either at position C5 and/or at position C2.…”
Section: Modifications At Position 34 (Table 2)mentioning
confidence: 99%